Chromosomal-Level Genome Assembly of the Springtail Tomocerus qinae (Collembola: Tomoceridae). (17th March 2022) - Pan, Zhixiang; Jin, Jianfeng; Xu, Cong; Yu, Daoyuan
Abstract: The family Tomoceridae is among the earliest derived collembolan lineages, thus is of key importance in understanding the evolution of Collembola. Here, we assembled a chromosome-level genome of one tomocerid species Tomocerus qinae by combining Nanopore long reads and Hi-C data. The final genome size was 334.44 Mb with the scaffold/contig N50 length of 71.85/13.94 Mb. BUSCO assessment indicated that 96.80% of complete arthropod universal single-copy orthologs ( n = 1, 013) were present in the assembly. The repeat elements accounted for 26.11% (87.26 Mb) and 494 noncoding RNAs were identified in the genome. A total of 20, 451 protein-coding genes were predicted, which captured 96.0% (973) BUSCO genes. Gene family evolution analyses identified 4, 825 expanded gene families of T. qinae, among them, 47 experienced significant expansions, and these significantly expanded gene families mainly involved in proliferation and growth. This study provides an important genomic resource for future evolution and comparative genomics analyses of Collembola.